PENGARUH KOMPRES DAUN KUBIS (BRASSICA OLERACEA) UNTUK MENGATASI BENDUNGAN ASI PADA IBU NIFAS - Anggriani, Yunita; Andri Kariny, Elsy Juni; Besmaya, Beniqna Maharani; C. Hardiyanti Rukmana (Jurnal Medicare, 2025)
Breast engorgement occurs due to obstruction of venous and lymphatic flow, leading to impaired milk drainage and increased pressure in the milk ducts and alveoli. One alternative to manage breast engorgement is the application of cabbage leaf compresses. This study aims to examine the effect of cabbage leaf compresses (Brassica oleracea) on reducing breast swelling and pain in postpartum mothers with breast engorgement. This research employed a quantitative method with a pre-experimental design (one group pretest-posttest) involving 33 respondents experiencing breast engorgement. Data were analyzed using the Wilcoxon test. The results showed a reduction in the average swelling score from 4.06 to 2.06 and a decrease in pain score from 3.58 to 2.94 after the intervention (p-value = 0.000). Cabbage leaf compresses were effective in reducing breast swelling and pain in postpartum mothers with breast engorgement. This method can be recommended as a non-pharmacological alternative in midwifery care.